Platanthera fujianense (Orchidaceae, Orchideae), a putatively holomycotrophic orchid from eastern China - Chen, Bing-Hua; Jin, Xiao-Hua (Phytotaxa, 2016)
Platanthera consists about 150–200 species and is among the largest terrestrial orchid genera; it is distributed across Asia, North America and Europe with a few species extending into North Africa and Central America (Bateman et al. 2003, 2009, Chase et al. 2015, Chen et al. 2009, Luer 1975, Pearce & Cribb 2002, Pridgeon et al. 2001, Lang 1999, Efimov 2016, Raskoti et al. 2016). There are about 50 species of Platanthera in China, out of which 25 species are endemic (Lang 1999, Chen et al. 2009, Jin et al. 2012, 2013,2014,2015, Efimov 2016). During fieldwork in eastern China, a leafless but visibly green Platanthera was discovered. This species is sympatric and similar to Platanthera minor, but it is easy to distinguish from the latter on the basis of vegetative and floral characters. Here we considered this little known Platanthera as a new species.